Applications of environmental aquatic chemistry : a practical guide - Weiner, Eugene R. (Boca Raton : CRC Press/Taylor & Francis Group, 2013)
"Updated and reorganized, this third edition provides the essential background for understanding and solving environmental chemistry problems that arise frequently. Aimed to help professionals deal with topical issues related to environmental chemistry, this book can also be used by students to gain a general understanding of the types of sectors and applications involved with environmental science. Several new chapters are included, covering topics such as algae growth, stormwater management, and wetlands. New case histories, which mainly illustrate treatment and remediation methods, are included. This edition also provides more end-of-chapter questions and answers. "--
"Preface to the Third Edition The chemical makeup of a collected water sample reflects the history of its prior flow path, particularly the minerals it has contacted, its contact time with these minerals, and the values of temperature, pH, and redox potential along the flow path. Many environmental chemistry books can be put into one of two groups: 1. Those that are very thorough and include nearly all of the basic chemical principles that underlie the topics covered. 2. Those that rely on an existing understanding of the basic principles and begin from there. This text tries to follow a middle path, where the basic principles needed for an environmental topic are included only to the extent of contributing to an understanding of the topic being discussed and to guide the reader in applying the information to actual environmental problems. The fields of environmental science and engineering advance rapidly. This third edition is substantially updated (Photo courtesy of Gary Witt) viii Preface to the Third Edition from the second edition. Besides extensive reorganization and updating, there is a new chapter "Nutrients and Odors: Nitrogen, Phosphorus, and Sulfur," two new appendices "Solubility of Slightly Soluble Metal Salts" and "Glossary of Acronyms and Abbreviations Used in this Book," and much new material, especially in Chapters 5 and 11 and in Appendix A. "--
Includes bibliographical references and index.
Keywords: Environmental chemistry; Water quality; SCIENCE / Chemistry / General; SCIENCE / Environmental Science; TECHNOLOGY & ENGINEERING / Environmental / Water Supply